Modification of kapok fibers via esterification for POME treatment: article - Idrus, Nur Nadirah; Alias, Nor Halaliza (2017)
Kapok fibers, the native of Central America is a good oil absorbent and low in cost. Adsorptive of oil in kapok fibers. The purpose of this study is to modified kapok fibers by esterification. The esterified kapok fibers were then test for POME treatment. Kapok fiber is one of natural fibers that have good hydrophobicity and buoyancy and is suitable for POME treatment specifically in term of oil adsorption. However due to increase its hydrophobicity, kapok fibers need to be modified. Based on the literature search, esterification of natural fibers can increase its ability to adsorb oil. Thus, in this research, the kapok fibers were esterified and oil removal test was conducted in order to see the effect of esterification of kapok fibers on its effectiveness to reduce the oil from POME. The esterification of kapok fibers were conducted at ration of kapok fibers to stearic acid by 1:1, 4:1 and 7:1. Effectiveness of kapok fibers to remove oil increase by 30 % after esterification. The oil and grease test shows that ratio kapok fibers to stearic acid by 4:1 gives 98.03 % of oil removal compared to 1:1 and 7:1 but it has very low different in percentage with 1:1. Water quality test such as BOD,COD,TSS and pH also conducted and shows that esterified kapok fibers gives better quality to POME. It decrease BOD by 76.90%, COD 67.84%, TSS 60.09 % and pH 21.21 %. The oil removal efficiency of kapok fibers successfully increased by esterification also help in increasing the quality of POME.